Bilateral abductor vocal cord palsy and pregnancy: a case report - Roslani, Annaliza; Raja Lope Ahmad, Raja Ahmad Al'konee; Yusof, Muhd Azlan; Yusuf, S.; Ismail, R. (Springer Verlag, 2012)

(untitled)
Bilateral abductor vocal cord palsy in pregnancy is a rare clinical problem. Due to the rarity of this condition, there is no definite guideline on obstetric management.